Minimally Invasive Treatment of Molar Incisor Hypomineralization Without Using Burs: Experiences via A Case Series in Vietnam - Ngoc, Võ Truong Nhu; Huyen, Nguyen Phương; Anh, Le Khả; Hang, Phan Thi Thu; Loan, Hoang Kim; Dong, Ta Thành (UI Scholars Hub, 2024)
Mild form of molar-incisor hypomineralization (MIH) on anterior teeth are posing great challenges to dental practitioners as it can have a huge aesthetic impact. In terms of deep MIH-related lesion below the healthy enamel, highly invasive methods for approaching the lesion body and removing the entire hypomineralized enamel using burs could lead to failures including aesthetic problems and even further tooth structure damage to the affected teeth. Case report: To resolve t his issue, we have proposed a modified resin infiltration technique based on the minimally invasive philosophy. In this study, we would like to report three specific cases about the use of the technique, which has the potential to restore the naturally aesthetic appearance for the anterior teeth while maintaining healthy tooth structure. Conclusion: Recovering the natural appearance of anterior teeth requires thorough attention to the aesthetics and integrity of the affected teeth. The proposed modified resin infiltration technique has been illustrated to bring back the natural morphology and maximally protect the healthy structure to ensure a long-term treatment outcome. The technique should be implemented to a significant degree for the long-term improvement in the oral health of pediatric patients in Vietnam and around the world.